An Extension of Strict Almost Contractions Employing Control Function and Binary Relation with Applications to Boundary Value Problems - Doaa Filali; Mohammad Akram; Mohammad Dilshad (Mathematics, 2023)
This article comprises some fixed point results for Boyd–Wong-type strict almost contractions using locally <semantics>L</semantics>-transitive binary relations. We provide several examples to illustrate our findings. On applying our results, we determine a unique solution of a special boundary value problem.